How can you learn general issues on occupational safety and health? A randomized controlled field trial research protocol for innovative training with gamification: let's play 626! - La Torre, Giuseppe; Capece, Guendalina; Shaholli, David; Nicolì, Francesca; Mannocci, Alice (Journal of Public Health: From Theory to Practice (2198-1833), 2026)
Aim: The objective of the study is to conduct a randomized controlled field trial to assess the efficacy of an intervention that includes a seminar and gamification session aimed at improving workers' knowledge on occupational security and health issues. Subject and methods: This study will be a two-center randomized controlled field trial (RCFT). A sample of employees from two universities will be recruited for the study. The intervention, called "Giochiamo a 626!" (Let's Play 626!), will be delivered as a one-day course, split into a seminar and a gamification session. Results: The sample will be randomly assigned to either a control group (CG) or an experimental group (EG). Both groups will attend the seminar, but only the EG will participate in the gamification session. The EG will test three different games. A questionnaire will be used to monitor the different levels of knowledge over time (T0 before the course, T1 after the course or game session). Conclusion: At the end of this trial, we plan to have developed active participation and emotional well-being in the classroom. Moreover, we expect that the number of correct answers to the questionnaire will significantly increase from T0 to T1 in the EG and will be the same in the control group.